2021
DOI: 10.3390/cancers13071693
|View full text |Cite
|
Sign up to set email alerts
|

Combination of PKCδ Inhibition with Conventional TKI Treatment to Target CML Models

Abstract: Numerous combinations of signaling pathway blockades in association with tyrosine kinase inhibitor (TKI) treatment have been proposed for eradicating leukemic stem cells (LSCs) in chronic myeloid leukemia (CML), but none are currently clinically available. Because targeting protein kinase Cδ (PKCδ) was demonstrated to eliminate cancer stem cells (CSCs) in solid tumors, we evaluated the efficacy of PKCδ inhibition in combination with TKIs for CML cells. We observed that inhibition of PKCδ by a pharmacological i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Muselli et al. ( 233 ) have recently shown that PKCδ regulates expression of the protein Bmi1 (B cell–specific Moloney murine leukemia virus integration site 1), which is required for stem cell renewal. Other prosurvival mechanisms include sequestration of Smac, an antagonist of inhibitor-of-apoptosis proteins ( Fig.…”
Section: Cell Survival and Cell Deathmentioning
confidence: 99%
“…Muselli et al. ( 233 ) have recently shown that PKCδ regulates expression of the protein Bmi1 (B cell–specific Moloney murine leukemia virus integration site 1), which is required for stem cell renewal. Other prosurvival mechanisms include sequestration of Smac, an antagonist of inhibitor-of-apoptosis proteins ( Fig.…”
Section: Cell Survival and Cell Deathmentioning
confidence: 99%
“…This Special Issue of Cancers , “PKs in leukemia”, had as objectives to present various clinical and biological aspects, but also to remind that PK pharmacological targeting is both of great interest and sometimes complicated or difficult to implement when harmful side effects occur. In this Special Issue, the benefit of inhibiting several kinases is reported in particular in chronic myelogenous leukemia (CML) to reduce the pool of residual leukemic stem cells [ 1 ]. However, therapeutic targeting by inhibition of PK may also be accompanied by adverse effects, as reported in CML for cardiac cytotoxicity [ 2 ].…”
mentioning
confidence: 99%
“…We will also see that many other PK can be targeted jointly or sequentially to avoid the emergence of resistance or increase the therapeutic potential of the treatments. We can then use combinations or multi-target inhibitors to increase [ 1 , 4 , 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation